2018
DOI: 10.1002/bio.3490
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Von Pechman synthesis of coumarin reaction for development of spectrofluorimetric method for quantitation of salmeterol xinafoate in pharmaceutical preparations and human plasma

Abstract: Simple, precise and selective spectrofluorimetric technique was evolved for quantitation of selective β agonist drug namely salmeterol xinafoate (SAL). Utilizing its phenolic nature, a method was described based on the reaction of the studied drug with ethyl acetoacetate (EAA) to yield extremely fluorescent coumarin product which can be detected at 480 nm (λ = 420 nm). The procedure obeys Beer's law with a correlation coefficient of r = 0.9999 in the concentration range between 500 and 5000 ng ml with and 177 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…[4,5] A carefully analytical survey revealed that several quantitative analytical procedures were announced for SAL determination in its pure form, commercial dosage form, and human plasma fluids. These methods include spectrophotometry, [6][7][8][9][10][11] spectrofluorimetry, [12] HPLC, [13][14][15][16][17][18] GC-MS, [19] and capillary electrophoresis. [20] All of the previous announced methods used for SAL analysis either need highly sophisticated instrumentation and tedious experimental procedures or lack adequate sensitivity as in spectrophotometric methods.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] A carefully analytical survey revealed that several quantitative analytical procedures were announced for SAL determination in its pure form, commercial dosage form, and human plasma fluids. These methods include spectrophotometry, [6][7][8][9][10][11] spectrofluorimetry, [12] HPLC, [13][14][15][16][17][18] GC-MS, [19] and capillary electrophoresis. [20] All of the previous announced methods used for SAL analysis either need highly sophisticated instrumentation and tedious experimental procedures or lack adequate sensitivity as in spectrophotometric methods.…”
Section: Introductionmentioning
confidence: 99%